Characterization and evaluation of patients anticoagulated with warfarin in relation to the complexity of pharmacotherapy - Mariana Pessoa de Sá; Flávia Fernandino Diniz; Leandro Pinheiro Cintra; Mayara Oliveira Ortiz; Renata Aline de Andrade; Maria Auxiliadora Parreiras Martins; Josiane Moreira da Costa (O Mundo da Saúde, 2023)
Diagnosis and treatment of sustained arrhythmias are part of the clinical routine, with one of the most frequent arrhythmias being Atrial Fibrillation (AF). To prevent thromboembolic events in patients with AF, oral anticoagulation is recommended, particularly warfarin. Despite its importance, this medication has a narrow therapeutic range, which means that small changes in treatment generate a risk of thrombotic or hemorrhagic events. Among these changes, adherence to other medications in use, changes in the use of these medications by prescribers and self-medication stand out. There are several interactions between warfarin and other medications for continuous use, with the belief that the complexity of the prescription may interfere with the clinical outcomes of anticoagulant therapy. The objective of the study was to characterize patients followed in an anticoagulation outpatient clinic in relation to the Pharmacotherapy Complexity Index. To identify the complexity of pharmacotherapy, prescriptions for other medications in use, prescribed by primary health care doctors, were considered. The Medication Regimen Complexity Index (MRCI) instrument was used. Complexity, understood as the form of administration, dosage and pharmaceutical form, factors that interfere with adherence to anticoagulant therapy, was subdivided into three complexity levels: low, moderate and high, as indicated in the literature. The complexity analysis was carried out by two researchers independently, considering the criteria as per MRCI guidance. This is a descriptive study carried out in two anticoagulation clinics, located in Minas Gerais. During the research, patients were monitored in two anticoagulation clinics in Brazil, using warfarin, and were invited to participate in a clinical trial between December 2018 and February 2019, and a selection was subsequently made for the present study. A total of 93 patients were included in the study, the average age was 63 years and the majority were female (68.8%). Atrial fibrillation was the most predominant OAC indication (92.5%). The average number of medications used was 7.0. The majority of patients with pharmacotherapy classified as high (38, 6.5%) and medium complexity (24, 80.7%) presented inadequate TTR. The present study identified that there is a predominance of patients with high complexity of pharmacotherapy, which may indicate the need for additional care in relation to anticoagulant treatment. Therefore, in cases of patients with inadequate control of oral anticoagulation, it is recommended that aspects of the complexity of pharmacotherapy be incorporated into the educational approach.